Surveillance of injecting‐related injury and diseases in people who inject drugs attending a targeted primary health care facility in Sydney's Kings Cross. (April 2015) - Ivan, Mihaela; van Beek, Ingrid; Wand, Handan; Maher, Lisa
Abstract Objective: This study examined the prevalence of injecting‐related injuries and diseases (IRIDs) and associated risk factors among people who inject drugs (PWID) attending a primary health care facility in Sydney's Kings Cross. Methods: We calculated prevalence of a wide range of IRIDs utilising data reported by 702 PWID who completed a clinician‐administered survey at their first visit. Multivariable logistic regressions identified factors independently associated with at least one episode of: i) cutaneous and ii) non‐cutaneous IRIDs. Results: Lifetime prevalence of cutaneous IRIDs was 23%. Forty‐two per cent of PWID with a history of abscess attended hospital at their most recent episode. Female gender, lifetime receptive syringe sharing (RSS), injecting while in custody, and ever injecting in places other than the arm were independently associated with reporting at least one episode of cutaneous IRIDs. Ever injecting in sites other than the arm, injecting for five or more years and lifetime history of RSS were independently associated with at least one episode of non‐cutaneous IRIDs. Conclusions: IRIDs are a substantial health issue for PWID. Their ongoing surveillance is warranted particularly in primary care settings targeting PWID to inform prevention and early management, thus reducing complications that may require hospital admission.